Conceptualization of disaster risk. Towards the Understanding of its construction - Mariela Vivier; Celia Torrens (Boletín Geográfico)
The conceptual review shows how the concept of risk has acquired complexity in its approach and construction, as the environmental situation of human settlements is also becoming more complex. The purpose of this article is to review the concepts related todisasterrisk -threatness, vulnerability, exposure and resilience- from a sociocultural perspective. This will make it possible to understand the interrelationships that exist between them in the process of construction of risk situations and, in later stages, to understand and explain the risk construction in the Neuquén ejido. In this context, it is the historical variable that establishes how the interaction between the natural environment and society in a region has developed, thus triggering dangerous situations for the population. It is explicit in the development of the work that the risk is the result of a social construction, in which, the physical conditions of nature are the trigger, but the process of occupation of the territories propitiates the existence of risk and disaster scenarios. When the action of men is present, risk is the product of the actions of a society that does not recognize and does not respect the laws of nature. Neuquén is an example of this. It has grown between planned neighborhoods, private homes and illegal settlements, many of which have occupied places naturally unsuitable for urbanization. The city shows that disorderly urban growth, the lack of mitigation works and the role of the State have led to the construction of vulnerabilities and the generation of situations of environmental risk that often end up materializing in a disaster with serious damage to homes, infrastructure of services, streets and people evacuated, as happened in the storm of April 2014, in which 80% of the urban plant was flooded with dissimilar consequences in the different sectors of the ejido.